Optimization of isocratic supercritical fluid chromatography for enantiomer separation - Chen, Wenda (2011)
This paper presents multi-objective optimization analysis and experimental implementation of a single column isocratic supercritical fluid chromatography process for the enantioseparation of flurbiprofen. The single column process is simulated using a detailed model with equilibrium description by a competitive Langmuir isotherm. The optimization problem has been formulated with the objectives of maximizing of productivity and minimizing solvent consumption under different product purity and recovery constraints. The solubility of the solute in the mobile phase is explicitly accounted in the problem formulation. The results showed a maximum productivity of 5 kg racemate/kg stationary phase / day with a corresponding organic solvent consumption of 80 L/kg racemate for a required purity and recovery of 95%. The optimal operating conditions have been experimentally implemented in an analytical scale laboratory set-up which support the optimization results.